PANDANGAN DUNIA JAWA DALAM TAFSIR INDONESIA: MENUSANTARAKAN PENAFSIRAN KLASIK DALAM TAFSIR BERBAHASA JAWA - Ghozali, Mahbub (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2020)
Acculturation between tafseer and tradition in Indonesia, like an aculturation between Islam and culture. The process of acculturation is successful. The dialogue between tradition and tafseer makes both of them not deny each other. However, the study about that, just strengthening the evidence from the results of the analysis about the products of interpretation. As a result, the study about interpretation in Indonesia become a repetitive study and only focuses on interpretation products. The development of an acculturative method that has proven successful, is more essential to provide new methods for interpretation in Indonesia. On these problems, this study aims to find the concept of acculturation in interpretations in Indonesia which makes classical interpretations as a reference. This research uses qualitative methods with literature study techniques. As a tool in analyzing data, this study also uses historical analysis with the approach of al-thÃ¢bit wa al-mutaá¸¥awwil and hermeneutics. The study found that the usage of classical interpretation is only used to find the moral ideal of a verse, which is then modified and interpreted according to the Javanese world view of the complex world. To modify this interpretation, Indonesian commentators do so by referring to three principles, namely conservative-reactionary, conservative-argumentative, conservative-reactionary